2020
DOI: 10.1111/his.14188
|View full text |Cite
|
Sign up to set email alerts
|

Malignant tumours of the uterus and ovaries with Mullerian and germ cell or trophoblastic components have a somatic origin and are characterised by genomic instability 

Abstract: Aims Tumours of the female genital tract with a combination of malignant Mullerian and germ cell or trophoblastic tumour (MMGC/T) components are usually diagnosed in postmenopausal women, and pursue an aggressive clinical course characterised by poor response to therapy and early relapses. These clinical features suggest that MMGC/T are somatic in origin, but objective molecular data to support this interpretation are lacking. This study evaluates the molecular features of nine MMGC/T, including seven tumours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…Recent studies genetically analyzed ovarian and uterine tumors with a combination of epithelial tumor components and YST or trophoblastic tumor components using targeted next-generation sequencing. [7][8][9] The findings obtained revealed that both components shared identical mutations that generally involved epithelial tumor development, such as PTEN, PIK3CA, KRAS, BRAF, CTNNB1, ARID1A, and TP53. [7][8][9] A mutation analysis of immature teratoma associated with an epithelial tumor had not been conducted until the present case.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Recent studies genetically analyzed ovarian and uterine tumors with a combination of epithelial tumor components and YST or trophoblastic tumor components using targeted next-generation sequencing. [7][8][9] The findings obtained revealed that both components shared identical mutations that generally involved epithelial tumor development, such as PTEN, PIK3CA, KRAS, BRAF, CTNNB1, ARID1A, and TP53. [7][8][9] A mutation analysis of immature teratoma associated with an epithelial tumor had not been conducted until the present case.…”
Section: Discussionmentioning
confidence: 90%
“…[7][8][9] The findings obtained revealed that both components shared identical mutations that generally involved epithelial tumor development, such as PTEN, PIK3CA, KRAS, BRAF, CTNNB1, ARID1A, and TP53. [7][8][9] A mutation analysis of immature teratoma associated with an epithelial tumor had not been conducted until the present case. Clear cell carcinoma and immature teratoma in the present case both showed the loss of ARID1A and an identical PIK3CA mutation, which are common abnormalities of ovarian clear cell carcinoma that frequently coexist.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These neoplasms usually occur in postmenopausal patients and exhibit an aggressive clinical behavior. [26][27][28][29][30][31][32][33][34] Several recent molecular studies have helped confirm a somatic origin of the germ cell component in these neoplasms given the similar mutational profiles in both tumor components, which have generally been those expected in the Mullerian component. Other features in favor of a somatic origin for the germ cell component include lack of i( 12)p (see below), their frequent presentation in postmenopausal women (an age group where germ cell tumors, especially YST, are uncommon) and their suboptimal response to germ cellrelated chemotherapy.…”
Section: Discussionmentioning
confidence: 99%